Yam propagation using Aeroponics technology - Maroya, N.; Balogun, M.; Asiedu, Robert; Aighewi, B.A.; Kumar, P. Lava; Augusto, J. (Sciencedomain International, 2014)
Aims: To study yam propagation and seed yam tuber production in aeroponics system.Study Design: The experiment was conducted in a randomized complete block designand treatments were replicated three times.Place of Study: This experiment was carried out at the International Institute of TropicalAgriculture Headquarters at Ibadan in Nigeria.Methodology: The experiment tested fresh vine cuttings of five yam genotypes of twospecies in an aeroponics system. Three genotypes of Dioscorea rotundata (TDr 89/02475,TDr 89/02665 and TDr 95/18544) and two yam genotypes of D. alata (TDa 98/01176 andTDa 291) were evaluated.Results: Vines of both D. rotundata and D. alata rooted within 2 weeks in aeroponicssystem. The rooting of vine cuttings varied significantly among genotypes with a maximumof 98% for TDa 98/01176 and a minimum of 68% for TDr 89/02665. Mini-tubers harvestedafter 4 months of growth in aeroponics weighed between 0.2 and 2.7g. A second harvest 6months later gave mini-tubers of up to 110g. The analysis of variance showed significantdifference (P<0.05) among genotypes for rooting at 2 weeks after vine planting, number ofplant surviving at 90 days after planting and percentage of plants with bulbils. The best genotypes were TDr 95/18544 and TDr 89/02665 for survival at 90 days after vine plantingand percentage of plant producing bulbils in the aeroponics system respectively.Conclusion: This study revealed that yam genotypes performed differently in aeroponicssystem for vine rooting and production of mini-tubers and bulbils.